2010
DOI: 10.1016/j.japwor.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Private capital flows, stock market and economic growth in developed and developing countries: A comparative analysis

Abstract: Empirically we investigate how three types of private capital flows could promote economic growth in recipient developed and developing countries. Our focus is on the role of stock markets as a channel through which foreign capital flows could promote growth. The findings reveal that FDI exhibits a positive impact on growth, while both foreign debt and portfolio investment have a negative impact on growth in all sample countries. However, our results indicate that stock markets might be a significant channel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 47 publications
9
90
1
1
Order By: Relevance
“…This result is consistent with some studies in the FDIgrowth literature (e.g. Chong et al, 2010;Gui-Diby, 2014). Meanwhile, the EF coefficient carries a positive sign and is statistically significant at conventional levels, implying that economic growth is stronger when EF is high because it makes investment more productive.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with some studies in the FDIgrowth literature (e.g. Chong et al, 2010;Gui-Diby, 2014). Meanwhile, the EF coefficient carries a positive sign and is statistically significant at conventional levels, implying that economic growth is stronger when EF is high because it makes investment more productive.…”
Section: Resultssupporting
confidence: 91%
“…Some studies in this literature have found that FDI exerts a positive impact on economic growth in the host countries (Chong et al, 2010;Gui-Diby, 2014), while others have found no such evidence or even a negative impact on economic growth (Ericsson and Irandoust, 2001). Drawing on the ambiguous and inconclusive results of the FDI-growth relationship, the literature has identified absorptive capacity of the host country as the key explanatory variable for the varied conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…As shown by the net positive effect result, this means an increase in the size of the stock market leads to better economic performance. The result is consistent with past studies (Levine & Zervos, 1998;Choong et al, 2010;Thumrongvit et al, 2013;Ngare et al, 2014). Based on the World Bank Report, the average value of Malaysian stock market capitalization as a percentage of GDP from 1988 to 2012 is 156.37 percent.…”
Section: A Spur To the Country's Economic Growth 59supporting
confidence: 91%
“…Previous studies provide evidence on the relationship between financial markets and economic growth (Levine & Zervos, 1998;Arestis, Demetriades, & Luintel, 2001;Enisan & Olufisayo, 2009;Azman-Saini et al, 2010;Choong et al, 2010;Thumrongvit et al, 2013;Ngare et al, 2014;Bayar, Kaya, & Yildirim, 2014). They show that a country's economic activities are significantly influenced by the development of the banking sector, the bond market and the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation